Instructional Supervision Factors Affecting Organizational Commitment of Thai Teachers: A Case Study of Amphur Mueang, Prachinburi Province, Thailand - Madriaga, Robina David (Journal of Education and Vocational Research, 2014)
This study is a descriptive research. The main purpose and objectives of this study were: 1) To determine the level of commitment of the teachers in terms of the three organizational commitment components namely affective, normative and continuance commitment; 2) To determine the level of instructional supervision as perceived by teachers in terms of its six factors namely inspection, assistance and support, oversight responsibilities, leadership skills, professional development, and collaboration; 3) To investigate the significance of instructional supervision factors affecting organizational commitment of Thai teachers. This study utilized descriptive method. The instrument employed for collecting the data was an opinionnaire regarding the factors of instructional supervision and components of organizational commitment developed by Baffour-Awuah (2011) and Meyer and Allen (1991).The statistics used for the treatment of data were mean, standard deviation (s.d.), standard error mean (s.e.mean), coefficient of variation (C.V.), and Multiple Regression Analysis. Results showed that two of the components of organizational commitment namely Affective Commitment and Normative Commitment are above the expected level or in high level, while Continuance Commitment is within the expected level or in moderate level. All six factors of instructional supervision are above the expected level or in high level. It was also found that among the six factors of instructional supervision, only two of them namely â€œAssistance and Supportâ€ and â€œLeadership Skillsâ€ significantly affect the organizational commitment of Thai teachers. The predictive equation is: Z (Organizati onalCommit ment ) = 59.506* + 1.748* (Assistance and Support) + 1.697* (Leadership Skills); R = 0.4710, F= 51.202* (10.025) (0.576) 2 (0.515)